(untitled) (Global Journal of Medical Research, 2014)
We reported a case of anterior inferior cerbellar artery infarction initially manifesting with positional vertigo ensuing from abrupt onset of hearing loss. A 56-year-old Taiwanese man suffering from controlled hypertension visited a local hospital because of a "rocking sensation." He was referred to the ear, nose, and throat (ENT) department for evaluation and was diagnosed with peripheral vertigo associated with positional change. Symptomatic treatment was administered, but produced a limited effect. He was then transferred to our hospital and was admitted to ENT services. The symptom was aggravated when the patient turned his head to either side or bent his neck forward. Two days after admission, he suffered from abrupt onset of hearing loss in the left ear. A neurologist was consulted. Neurological and physical examinations revealed unremarkable findings, except for sensorineural type hearing impairment in the left ear.